Expression of parlour behaviour, temperament, welfare and approach test in postpartum Surti buffaloes (Bubalus bubalis) - K R RSRIRANGA; T K S RAO; K R HARINI; R R SINGH; N B PATEL (Indian Journal of Animal Sciences, 2023)
The present study was carried out at Livestock Research Station, Navsari Agricultural University, Navsari, Gujarat to investigate the effect of parity on milking parlour behaviour, temperament and welfare of postpartum Surti buffaloes. Fourteen postpartum Surti buffaloes were selected and grouped based on parity as primiparous and multiparous (2nd to 5th lactation). The milking behaviour of experimental animals was observed on the day of calving, 7th, 15th, 30th, 45th, 60th and 80th day post-calving keeping in view the peak production of buffaloes. The primiparous animals showed higher milk let down time and milking time, and lower rate of milk flow as compared to multiparous animals. The frequency of incidences of urination, defecation, kicking and stepping were significantly higher in primiparous group. The primiparous animals exhibited more avoidance behaviour when approached by a test person, indicative of more agitation. During milking and in paddock, primiparous animals were more aggressive and restless as compared to multiparous animals which exhibited calmer and docile temperament. From the present study, it could be conferred that parity significantly influences the parlour behaviour, temperament and welfare in postpartum Surti buffaloes.